2010
DOI: 10.1186/1471-2164-11-98
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of Actinobacillus pleuropneumoniae during the acute phase of a natural infection in pigs

Abstract: BackgroundActinobacillus pleuropneumoniae is the etiological agent of porcine pleuropneumonia, a respiratory disease which causes great economic losses worldwide. Many virulence factors are involved in the pathogenesis, namely capsular polysaccharides, RTX toxins, LPS and many iron acquisition systems. In order to identify genes that are expressed in vivo during a natural infection, we undertook transcript profiling experiments with an A. pleuropneumoniae DNA microarray, after recovery of bacterial mRNAs from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
67
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 81 publications
8
67
0
Order By: Relevance
“…This result is in accordance with a previous study, which showed that the type IV fimbrial promoter is induced upon contact with host cells via the luxAB reporter system (22). Besides, two recent studies that looked at A. pleuropneumoniae gene expression during natural and experimental infections in pigs also indicated the upregulation of genes coding for type IV fimbriae (36,37).…”
Section: Figsupporting
confidence: 80%
“…This result is in accordance with a previous study, which showed that the type IV fimbrial promoter is induced upon contact with host cells via the luxAB reporter system (22). Besides, two recent studies that looked at A. pleuropneumoniae gene expression during natural and experimental infections in pigs also indicated the upregulation of genes coding for type IV fimbriae (36,37).…”
Section: Figsupporting
confidence: 80%
“…We used aerobiosis as it is the typical atmosphere used in experiments involving A. pleuropneumoniae and anaerobiosis as, based on mutant Jacobsen et al 2005;Buettner et al 2009) or transcriptome (Deslandes et al 2010;Klitgaard et al 2012) studies, it is representative of the growth conditions found in necrotic lungs of pigs. As shown in Figure 4 and Table 1, some trans-acting sRNA candidates, like Arrc05 and Arrc08, are located between genes within operons, which could allow them to be mistaken for subproducts of polycistronic mRNA maturation.…”
Section: Discussionmentioning
confidence: 99%
“…pleuropneumoniae is the etiologic agent of porcine pleuropneumonia in hyperacute, acute or chronic form [36]- [40]. Positive results based on the apxIV gene amplification indicate the presence of this bacterium in almost all samples, with the exception of urine samples.…”
Section: Discussionmentioning
confidence: 99%